2013
DOI: 10.1002/etc.2087
|View full text |Cite
|
Sign up to set email alerts
|

Biochar‐mediated reductive transformation of nitro herbicides and explosives

Abstract: Abstract-Biochar, a subset of black carbon produced via pyrolysis of biomass, has received much attention in recent years due to its potential to address many important issues, from energy and climate to agriculture and environmental quality. Biochar is known to influence the fate and transport of organic contaminants, although its role has been generally assumed to be as an adsorbent. In this study, the authors investigated the ability of biochar to catalyze the reductive reactions of nitro herbicides and exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 129 publications
(62 citation statements)
references
References 34 publications
2
59
0
1
Order By: Relevance
“…5). This is consistent with the previously reported biochar-dithiothreitol-DNT system (Oh et al, 2013b). Copyrolyzed biochar with PS/PE and RS also showed similar results (data not shown).…”
Section: Reduction Of Dnt By Dithiotreitol With Polymer/rs-derived Bisupporting
confidence: 94%
“…5). This is consistent with the previously reported biochar-dithiothreitol-DNT system (Oh et al, 2013b). Copyrolyzed biochar with PS/PE and RS also showed similar results (data not shown).…”
Section: Reduction Of Dnt By Dithiotreitol With Polymer/rs-derived Bisupporting
confidence: 94%
“…In this process, a suitable magnetic oxide (namely, iron oxide) and its composite are used for PS oxidation to yield an effective reactive species because iron oxide is a more effective and stable catalyst as compared to soluble Fe 2+ ions for the catalytic oxidation of organic pollutants [9][10][11]. Biochar is a readily available porous carbonaceous material that is produced as a solid by-product by the thermal decomposition of organic materials under oxygen-limited conditions and subsequent modification by chemical and physical methods [12]. Biochar is used widely as a soil additive, for nutrient retention in agriculture, for the adsorption of metallic and organic contaminants in sediments, as an energy generation co-product, and for mitigating climate change, because of its wide availability, low cost, and environmental friendliness [13].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that biochar contains persistent free radicals (PFRs), which exhibited the ability to activate oxygen for the generation of reactive oxygen species and degraded contaminants efficiently (Fang et al 2014(Fang et al , 2015. Moreover, these PFRs also exhibited the ability to mediate the electron transfer reactions, which would mediate the reductive degradation of contaminants (Oh et al 2013;Klüpfel et al 2014). Although the concentrations of detected high-chlorinated PCBs changed slightly in soils, other highchlorinated PCBs could also existe in this contaminated soil, and their concentrations were not quantified due to the lack of standards.…”
Section: Effect Of Biochar/ac Enrichment On Bioaccumulation Of Pcbs Bmentioning
confidence: 99%